THE The Effect Of Perceived Ease Of Use, Perceived Usefulness, Perceived Security, And Perceived Credibility Mobile Banking As A Digital Payment On The Financial Management Of Undergraduate Accounting Students At State Universities In Surabaya - Rizky Embun Arifah; Tituk Diah Widajantie (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to analyze and empirically prove the effect of perceived ease of use, perceived usefulness, perceived security, and perceived credibility mobile banking as a digital payment on the financial management of undergraduate accounting students at State Universities in Surabaya. This type of research is quantitative research with primary data obtained through questionnaires. The population were undergraduate accounting students at State Universities in Surabaya. The sample was determined using a probability sampling technique with a simple random sampling method so that a sample of 98 respondents was obtained. The analysis technique for this research uses the Partial Least Square (PLS) method and was tested using the SmartPLS 4 program. The research results show that perceived ease of use, perceived usefulness, and perceived security has a positive and significant effect on financial management, while perceived credibility has a positive but not significant effect on financial management.Keywords: Perceived Ease of Use, Perceived Usefulness, Perceived Security, Perceived Credibility, Financial Management